2020
DOI: 10.15346/hc.v7i1.111
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Crowdsourcing in Medical Image Analysis

Abstract: Rapid advances in image processing capabilities have been seen across many domains, fostered by the  application of machine learning algorithms to "big-data". However, within the realm of medical image analysis, advances have been curtailed, in part, due to the limited availability of large-scale, well-annotated datasets. One of the main reasons for this is the high cost often associated with producing large amounts of high-quality meta-data. Recently, there has been growing interest in the application of crow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 67 publications
(246 reference statements)
0
6
0
Order By: Relevance
“…Our results provide justification toward using large-scale nonexpert contours for gold-standard segmentation data in the absence of multiple expert “ground truth” data availability, and glean insight into the behavior of consensus contours across a large number of observer inputs. Although crowdsourcing is common in medical image analysis, 31 there have been few studies evaluating the use of crowdsourcing for contour quality. To our knowledge, this is the largest study characterizing segmentation performance across multiple physician observers, and the first study to investigate crowdsourced contour performance in the context of radiation oncology workflows.…”
Section: Discussionmentioning
confidence: 99%
“…Our results provide justification toward using large-scale nonexpert contours for gold-standard segmentation data in the absence of multiple expert “ground truth” data availability, and glean insight into the behavior of consensus contours across a large number of observer inputs. Although crowdsourcing is common in medical image analysis, 31 there have been few studies evaluating the use of crowdsourcing for contour quality. To our knowledge, this is the largest study characterizing segmentation performance across multiple physician observers, and the first study to investigate crowdsourced contour performance in the context of radiation oncology workflows.…”
Section: Discussionmentioning
confidence: 99%
“…Several projects have developed techniques to generate synthetic training datasets, consisting of pairs of synthetic tissue images and masks, for image segmentation ( Hossain and Sakib 2020 ; Gong et al 2021 ). Crowdsourcing approaches also have been implemented to curate large training datasets ( Li and Deng 2018 ; Ørting et al 2019) .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple projects to date have demonstrated that citizen scientists can be effectively engaged in a wide variety of biological image analysis tasks, such as the tracing of connected neurons through electron microscopy (EM) data in Eyewire (Kim et al, 2014), clicking on protein particles in cryo-EM data in Microscopy Masters (Bruggemann et al, 2018), and scoring tumor markers in pathology samples in Cell slider (Dos Reis et al, 2015), amongst others (Smittenaar et al, 2018;Ørting et al, 2019;Benhajali et al, 2020;Fisch et al, 2021;Fowler et al, 2022). The efficacy of applying online citizen science for the analysis of biological image data, both as an avenue for producing novel research and as a powerful tool for public engagement, has led to a rise in interest from the biological volumetric imaging research community in applying this methodology.…”
Section: Introductionmentioning
confidence: 99%